An analysis of the challenges faced by small scale chrome miners in Zimbabwe - Nyamwanza, Tonderai; Mavhiki, Severino; Mapetere, Denver; Dandadzi, Johnson (Midlands State University, 2015)
The Government of Zimbabwe introduced a ban on the exportation of chrome after exporters had failed to acquire technology for the local processing of the mineral. Following the ban, many players adopted various strategies to ensure that they continued to benefit from the extraction and exploration of the mineral. Among the efforts were efforts to have the ban lifted so that miners would sell the unprocessed chrome. The study sought to establish the effectiveness of the strategies adopted by the small scale tribute miners following the ban. The findings of the study were that the production rates had fallen and there was lack of capacity by smelting companies to take all the ore. Low prices offered by the smelting companies’ together with the high operational costs forced some small scale miners to divest into gold mining and others to scale down their operations.